Optimal Range of Lymphadenectomy in Pathological Stage T1 and T2 Esophageal Squamous Cell Carcinoma - Wu, Hansheng; Zhuang, Weitao; Huang, Shujie; Guan, Xueting; Zheng, Yuju; Xie, Zefeng; Chen, Gang; Tang, Jiming; Zhou, Haiyu; Xie, Liang; Ben, Xiaosong; Zhou, Zihao; et al. (Frontiers in Oncology, 2021)
Background: Although lymph node contributes to tumor progression and metastasis in esophageal squamous cell carcinoma (ESCC), the optimal extent of lymphadenectomy during esophagectomy is currently a topic of controversy. This study aimed to investigate the appropriate number of lymph node dissected in pT1-2Nany stage ESCC to achieve the best prognosis and avoid missing positive lymph nodes (PLNs). Methods: A total of 497 patients with pT1 to pT2 esophageal cancer from two institutions were retrospectively analyzed, with their surgical and pathological records being reviewed critically. Stepwise analyses were conducted by calculating a serial of hazard ratios and odd ratios, to determine the optimal range of lymphadenectomy for overall survival (OS). Results: The best survival outcome can be obtained when the number of lymph node examined (NLNE) is 10-18 in pT1N0 ESCC, while the NLNE should exceed 24 in pT2N0 diseases. In patients with pT1-2Nany and pT2Nany ESCC, resection of 15-25 and 24-37 lymph nodes, respectively, could provide significant added value for finding the positive nodal metastasis. When the NLNE exceeding this appropriate range, each extra lymph node resection is not helpful to improve the probability of finding PLNs. Conclusions: For ESCC patients undergoing radical esophagectomy, the optimal extent of lymphadenectomy is 15-25 for pT1Nany diseases, and 24-37 for pT2Nany diseases.